Odpowiedzi

2010-01-11T17:13:18+01:00
A) 3x=12/3
x-y=1

x=4
4-y=1

x=4
-y=1-4 /*-1

x=4
y=3

b)5y=2/5
x+y=0,02

y=2/5
x+2/5=0,02

y=0,4
x=0,02-0,4

y=0,4
x=-0,38

c)17y=0/17
4y-u=6

y=0
4*0-u=6

y=o
-u=6/*(-1)

y=0
u=-6
2010-01-11T17:19:39+01:00
A)
3x = 12
x - y = 1 /*(-3)

3x=12
-3x+3y=-3
___________

3y=9 /:3
y=3

y=3
x=4

b)
5y = 2
x + y = 2⅖/*(-5)-----> (2i2/5) to (2,4) :P

5y=2
-5x-5y=-12
_____________

-5x=-10/:(-5)
x=2

2+y=2,4
2,4-2=y
y=0,4

c)
4y - u = 6
17y = 0/:17

4y-u=6
y=0

0-u=6
u=6